2015
DOI: 10.1088/0953-8984/27/7/072202
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in thermoelectric SnSe at high pressures

Abstract: Abstract. The crystal structure of the thermoelectric material tin selenide has been investigated with angle-dispersive synchrotron x-ray powder diffraction under hydrostatic pressure up to 27 GPa. With increasing pressure, a continuous evolution of the crystal structure from the GeS type to the higher-symmetry TlI type was observed, with a critical pressure of 10.5(3) GPa. The orthorhombic high-pressure modification, β -SnSe, is closely related to the pseudo-tetragonal high-temperature modification at ambient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 35 publications
16
69
0
Order By: Relevance
“…As expected, SnSe goes through a phase transition from the P nma structure through Cmcm to a higher symmetry B2 structure with increasing pressure. The high-pressure crystal structures and the corresponding phase transition pressures are in good agreements with experimental observations [6,7], indicating the reliability of our calculations. SnSe 2 has a CdI 2 -type structure with a space group of P3m1 at 0 GPa, and it transforms to the R3m space group at 5 GPa.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…As expected, SnSe goes through a phase transition from the P nma structure through Cmcm to a higher symmetry B2 structure with increasing pressure. The high-pressure crystal structures and the corresponding phase transition pressures are in good agreements with experimental observations [6,7], indicating the reliability of our calculations. SnSe 2 has a CdI 2 -type structure with a space group of P3m1 at 0 GPa, and it transforms to the R3m space group at 5 GPa.…”
supporting
confidence: 85%
“…SnSe is a narrow band gap semiconductor with an unprecedented thermoelectric efficiency [4,5]. It was shown that laminar SnSe (B16-type structure in the P nma space group) undergoes a pressure-induced structural phase transition to the B33 structure (Cmcm space group) at about 10.5 GPa [6]. Under further compression, SnSe transforms to the B2 structure (P m3m space group) and this phase was found to exhibit a superconducting transition at low temperatures above 58 GPa [7].…”
mentioning
confidence: 99%
“…This phase transition has been the subject of a number of early crystallographic and thermomechanical experimental investigations [22][23][24][25][26][27][28][29][30][31]. More recently, the ultra-low lattice thermal conductivity of SnSe has attracted great interest for thermoelectric applications, and has been studied both experimentally and through ab-initio simulations [10,[18][19][20][32][33][34][35][36][37][38][39][40][41][42]. The coupling between lattice distortion and electronic structure was recently shown to be responsible for the large anharmonicity, which persists in a broad range of temperatures, and leads to the low thermal conductivity [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to further optimize the performance and extend the range of working temperature of SnSe, several approaches have been explored, for example, hole doping [1], applying hydrostatic pressure [7,8], and nanostructuring [9,10]. Another important alternative is strain-engineering, which has long been used as an effective and predictable means for tuning the materials properties [11][12][13][14][15][16], including strain-induced structural phase transitions [17][18][19], indirect-direct band gap transition [11][12][13], and semiconductormetal transition [12,20].…”
Section: Introductionmentioning
confidence: 99%